2018
DOI: 10.1136/heartjnl-2018-313439
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk model performance in women with and without hypertensive disorders of pregnancy

Abstract: SCORE performed best in terms of both calibration and discrimination, while FRS and PCEs overpredicted risk in women with and without hHDP, but improved after recalibrating and refitting the models. No separate model for women with hHDP seems necessary, despite their higher baseline risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…All studies showed an increased unadjusted CVD risk in women with previous HDP, but previous HDP did not add to CVD risk prediction after adjustment for traditional CVD risk factors. 3133 All of these studies were limited by not assessing CVD risk in women <40 years of age, and the study by Stuart et al. interestingly indicated that previous HDP may add to CVD prediction in women aged 40–49 years.…”
Section: Discussionmentioning
confidence: 99%
“…All studies showed an increased unadjusted CVD risk in women with previous HDP, but previous HDP did not add to CVD risk prediction after adjustment for traditional CVD risk factors. 3133 All of these studies were limited by not assessing CVD risk in women <40 years of age, and the study by Stuart et al. interestingly indicated that previous HDP may add to CVD prediction in women aged 40–49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for effective primary prevention at the time of, or following, maternity care it is important that all risk factors for CVD are considered and not only those directly pregnancy-related. Dam et al [44] investigated the performance of three commonly used CVD risk prediction models (SCORE, Framingham risk score, and Pooled Cohorts Equation) in women with a history of HDP and compared the performance to women with only normotensive pregnancies. They found the predictive performance of all models to be similar regardless of HDP history.…”
Section: Current Gap Of Knowledgementioning
confidence: 99%
“…Therefore, adding HDP to existing CVD risk prediction models does not seem to improve performance of the score because the predictive models work well already. 12 Once again, as epidemiologists, we are not surprised by the results of the Moe study and their final suggestion to use single markers rather than complex scores. In previous times, when the so-called metabolic syndrome was accepted by most, we suggested in countertrend the concrete possibility that it was nothing more than a constellation of markers, 13 like a whole orchestra that sounds very good, but in which, nevertheless, every single musical instrument is playing exactly the same music.…”
Section: A Commentmentioning
confidence: 94%
“…The well-known epidemiological CVD risk observed by other authors within 10 years after delivery in women with HDP or GDM is only marginally reflected by the calculation of long-term CVD risk. 12 It is substantially superfluous to go in search of such sophisticated scores given that ultimately, upon admission of the authors themselves, the scores added no conclusive information to the question on whether after one year from the delivery the mother has or not an increased risk of CVD. The reason for these results could be that female-specific factors, such as HDP and GDM, increase the risk of CVD through increasing the levels of the traditional cardiovascular risk factors already included in the score models.…”
Section: A Commentmentioning
confidence: 99%
See 1 more Smart Citation